2017
DOI: 10.12968/bjmh.2017.6.1.6
|View full text |Cite
|
Sign up to set email alerts
|

A new beginning or the end of the old order?

Abstract: This commentary explores the Government's apprenticeship reform programme

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…These have already been identified by the Government as a key area of focus. Recent world events have suggested that political and social upheaval and incidents may, in part, be due to or exacerbate existing mental health issues and potentially cause new problems (McIntosh & McClelland, 2017). The media (in all its forms) plays a role in highlighting fearprovoking events.…”
mentioning
confidence: 99%
“…These have already been identified by the Government as a key area of focus. Recent world events have suggested that political and social upheaval and incidents may, in part, be due to or exacerbate existing mental health issues and potentially cause new problems (McIntosh & McClelland, 2017). The media (in all its forms) plays a role in highlighting fearprovoking events.…”
mentioning
confidence: 99%